Genre-Based VS Problem-Based Approaches: A Comparative Study in English Classrooms for Junior High School Contexts - Istifadah; Ulin Nuha Annafiah, Afiya; Zahrani Firsta, Fanisa; Bisriyah, Maslihatul (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2024)
Approaches, strategies, and methods are significant elements that highly divine the successful teaching and learning process. Having been concerned with two different teaching approaches, this research study aimed to explore the comparison between the Genre-Based Approach (GBA) and Problem-Based Learning (PBL) implementation in English subjects for junior high school students. This research used a comparative descriptive study located at MTs Negeri 1 Malang and MTs Negeri 2 Malang. In-depth interviews and direct observations were two primary data collection techniques in this research. The data analysis was conducted using data reduction, presentation, and conclusion. The findings revealed key distinctions in implementation: GBA at MTsN 1 Malang followed four stages (BKoF, MoT, JCoT, and ICoT) with modifications like peer-review activities and interactive modeling, which enhanced students’ listening, writing, speaking, and collaboration skills. In contrast, PBL at MTsN 2 Malang emphasized critical thinking through authentic problem-solving tasks in five stages, including guided investigations, group presentations, and reflections, which fostered critical thinking, communication, and cooperation. Both methods were effective in improving English skills and fostering collaboration, though GBA focused more on building individual understanding, while PBL prioritized problem-solving and group interaction.